Peran Guru dalam Mengembangkan Strategi Pembelajaran Adaptif pada Pendidikan Islam di Era Merdeka Belajar - Rozan Taqi Junatama; Muhammad Zakry Ramadhan; Gusmaneli Gusmaneli (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to analyze the role of teachers in developing adaptive learning strategies within the context of Islamic education in the Merdeka Belajar era. Adaptive learning, which considers students' differing characteristics, needs, and learning styles, is considered essential for enhancing the quality of Islamic education. Using a literature review approach, this research examines various literatures related to the implementation of adaptive learning strategies, teacher competencies, and their implications on student learning outcomes and character development. The findings show that the pedagogical, social, professional, and personal competencies of teachers are crucial to the success of adaptive learning. The application of this strategy also leads to increased motivation, active participation, and the development of students' character and spirituality in Islamic education. Adaptive learning creates an inclusive, responsive environment that focuses on students' needs, which in turn improves the overall quality of education.